Bankruptcy Prediction Analysis of PT Jembo Company Tbk 2018-2022 - Erlynna, Nur; Ersianti, Junillah; Zennita, Laurencia; Wulandari, Putri (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2023)
This research aims to report financial analysis and predict potential bankruptcy at PT Jembo Company TBK which is listed on the Indonesian stock exchange. Data was obtained from the website of the Indonesia Stock Exchange which uses the financial reports for 2018, 2019, 2020, 2021, and 2022 using the Altman Z-score method. This research is a quantitative descriptive research that is used to analyze the financial statements of PT Jembo TBK. The results show that based on the Altman Z-score analysis, PT Jembo is projected not to experience bankruptcy during the 2018-2022 period because the average value is Z-> 1.1. This shows that the company is in a safe condition with the risk of bankruptcy until it is healthy.